Immediate dilation of a tight or stenotic cervix by intra-procedural administration of hyoscine butylbromide: A clinical trial - Shiva Hadadianpour; Shahrzad Tavana; Anahita Tavana; Masoumeh Fallahian (Shahid Sadoughi University of Medical Sciences, 2019)
Background Cervical dilation is indicated prior to performing various gynecological procedures. However, gynecologists are at times confronted with a stenotic or tight cervix, resistant to dilation. This can be problematic particularly when cervical ripening has not been attempted hours before the start of the procedure. Objective The objective of this study is to investigate the efficacy of administration of hyoscine butylbromide for cervical dilation for immediate dilation of the tight or stenotic cervix. Materials and Methods In this clinical trial study, a population of 40 women, aged 20-70 yr with stenotic cervix, evidenced by resistance to pass dilator #2 through their cervical canal were compared. Cervical patency was assessed 10 min following intra-cervical canal instillation of hyoscine butylbromide. Results Cervical width of 57.5% of patients became wider, as evidenced by passage of the number 4 Hegar dilator through the cervical canal without resistance. Independent T-tests did not reveal any statistically significant difference between the two groups based on their age. Fisher Exact test revealed a statistically significant difference between the two groups based on the prior route of delivery, with a more statistically significant response in patients who had vaginal deliveries. Conclusion Intra-cervical canal instillation of hyoscine butylbromide is effective in immediate dilation of the tight or stenotic cervix during intra-uterine procedures.